Assessing the Effects of Asset Price Bubbles on Industrial Economics - Blank, Justin (Université d'Ottawa | University of Ottawa, 2008)
Asset price bubbles are a phenomenon that have been around for over four centuries. Yet, there remain many unanswered questions regarding their presence. This paper reviews several definitions and methods to identify asset price bubbles. After presenting